Faktor Determinan Struktur Modal Bank yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Mardianto Mardianto; Gun Gun Budiarsyah (Pusat P2M Politeknik Negeri Batam, 2021)
This research aims to analyze the effect of profitability, asset structure, liquidity, dividend payout ratio (DPR), non debt tax shield (NDTS), growth, company age, and company size on bank leverage. This study relate the empirical findings and try to confirm with pecking order theory or trade-off theory. The research sample is banks in Indonesia which are listed on the Indonesia Stock Exchange for the period 2015-2019 and using multiple linear regression techniques. An appropriate level of profitability, asset structure as collateral with low value, high level of liquidity show conformity to the pecking order, which are negative and significant to bank leverage. DPR as a signal of income prospects and company size shows conformity with trade-off theory, which is positive and significant to bank leverage. Meanwhile, NDTS which shows a decrease in fixed collateral assets, asset growth and bank age do not have any significant effect with bank leverage. If the findings of age and size are compared, it shows that bank leverage does not depend on how long it has been operating, but assets size are more considered. This research fills in the gaps in the research on the determinants of bank leverage, including examining the variables of DPR, NDTS, and bank age which are rarely studied. In the future, the determinant of leverage may consider the agency theory, potential bankruptcy, corporate governance, ownership structure, and macroeconomic conditions.